Model Penerapan Asas Pemisahan Horizontal Dalam Lelang Eksekusi Hak Tanggungan - Widyastuti, Tiyas Vika; Indriasari, Evy; Pratama, Erwin Aditya; Siswanto (Diktum: Jurnal Ilmu Hukum, 2021)
The purpose of this study is to examine the implementation and model of the principle of horizontal separation in the granting of dependent rights in the community, issues related to the Deed of Encumbrance of Dependent Rights, that land rights can be considered as proof of ownership of everything that stands on the land. The research method uses a type of literature research, with a statutory approach, secondary data suber, descriptive analytical data analysis. The results of the study showed. Based on the principle of horizontal separation according to the UUPA, proof of ownership of the right to the land does not necessarily become proof of ownership of everything that consists of the land. This can give the holder ownership authority over the land only to the extent of the land surface, while the building or anything attached to the land is different from the ownership rights of the land. However, until now, this proof of ownership of land rights has always been considered to be evidence of ownership of anything that stands horizontally as regulated by the UUPA and which should be applied, but the encumbrance of Dependent Rights in Land Rights, still shows the application of the principle of vertical attachment to land certificates. A written agreement between the landowner and the owner of the building on it is an appropriate model in the application of the principle of horizontal separation in execution auctions under the Dependent Rights Act, as the agreement will apply as a law to those who agree.